Measurement of inclusive K*(0)(892), phi(1020) and K-2*(0)(1430) production in hadronic Z decays - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; et al. (1996)
The inclusive production of the neutral vector mesons K*0(892) and φ(1020), and of the tensor meson K2*0(1430), in hadronic decays of the Z has been measured by the DELPHI detector at LEP. The average production rates per hadronic Z decay have been determined to be 0.77 ± 0.08 K*0(892), 0.104 ± 0.008 φ(1020) and 0.079 ± 0.040 K2*0(1430). The ratio of the tensor-to-vector meson production yields, 〈K2*0(1430)〉/〈K *0(892)〉 = 0.10± 0.05, is smaller than the 〈f2(1270)〉/〈ρ0(770)〉 and 〈f2′(1525)〉 /〈φ(1020)〉 ratios measured by DELPHI. The production rates and differential cross sections are compared with the predictions of JETSET 7.4 tuned to the DELPHI data and of HERWIG 5.8. The K*0(892) and φ(1020) data are compatible with model predictions, but a large disagreement is observed for the K2*0(1430).